Influence of aggregate surface treatment on corrosion resistance of cement composite under chloride attack. (10th July 2020) - Sun, Dandan; Shi, Huisheng; Wu, Kai; Miramini, Saeed; Li, Binbin; Zhang, Lihai
Highlights: Effects of aggregate coating on the ITZ microstructure were tested and modelled. Coating on aggregate could reduce the porostiy in ITZ, ultimately inhibit the chloride ingression. Silica fume coating can significantly reduce the porosity in ITZ. Slag and silica fume coating could prolong the initiation corrosion time of reinforcement. Abstract: The high porosity of interfacial transition zone (ITZ) could significantly influence the durability of offshore concrete structures. This study aims to investigate the effects of aggregate surface by coating slag and silica fume on the ITZ microstructure, ultimately the corrosion resistance of the cement composite materials exposed to chloride attack. First, a series of experimental studies on chloride transport were carried out. Then, an experimentally validated model was developed to further understand the fundamental reactive-transport behaviour of chlorides in concrete in relation to different aggregate surface coating methods. The experimental results show that aggregate surface coating using silica fume can significantly reduce the porosity of interfacial transition zone ( e.g. more than 40% reduction of porosity 5 μm from aggregate surface). Most importantly, the numerical predictions indicate that the slag and silica fume coating could potentially prolong the initiation time of the steel bar corrosion in offshore structures by more than 60% and 170%, respectively.